Complejo Acinetobacter baumannii-calcoaceticus epidemiología y mecanismos de resistencia: Revisión sistemática - Cumbicus Cabrera, Jimi Sebastian (2024)
Antimicrobial resistance is a public health issue that demonstrates the ability of microorganisms to adapt and evade the effects of antibiotics, and Acinetobacter baumannii is no exception. Therefore, this systematic review was conducted to describe the risk factors associated with infection by this bacterium and the resistance mechanisms it expresses. The search was carried out in databases such as PubMed, Scielo, BVS, and Scopus, using search combinations with the terms "risk factor", "epidemiology", "resistance", "antimicrobial drug resistance" to select freely accessible observational studies published in the last 10 years. A total of 1,732 studies were retrieved; after removing duplicates, grey literature, paid articles, and applying inclusion criteria, 19 articles were selected. Their quality was assessed using the Joanna Briggs Institute (JBI) tool, where 89.47% of the articles were found to have low bias, and 10.53% had moderate bias. The main risk factors for developing infections from the A. baumannii complex were described as prolonged hospital stay, immunosuppressed patients, and the use of invasive medical devices. Frequently described resistance mechanisms include the presence of chromosomal and acquired carbapenemases, as well as the production of extended-spectrum beta-lactamases. Given the broad spectrum of antibiotics affected by these mechanisms, their early detection and the implementation of antibiotic stewardship programs are essential to reduce the occurrence of these infections and mortality